Papillary urothelial neoplasm of low malignant potential with osseous metaplasia in a 19-year-old chronic smoker: A case report with review of literature - Rakesh K Gupta; Poonam Wasnik; Amit R Sharma (Wolters Kluwer Medknow Publications, 2024)
Urothelial tumors characteristically occur in elderly persons, more commonly in males with typical complaints of hematuria. Although few studies attempted to describe clinic-pathological features of urothelial malignancies in young patients, due to heterogeneity in the inclusion of age groups under "young patients" no reliable conclusions can be derived. Herein, we are describing an interesting case of papillary urothelial neoplasm of low malignant potential with osseous metaplasia in a 19-year-old chronic smoker young patient presented with chief complaints of abdominal pain with a review of the literature.